Of Dr. Jawad Ali and his scientific efforts - alkhafagy, Eman S. (Humanities Journal of University of Zakho, 2013)
To start with, it is worth saying that Jawad Ali is a truly native Arab man who was born in 1907 AD. and died in 1987.Jawad Ali, in fact, has a great effect in the society where he lived and in the high school of teachers where he studied. He used to study and write than to enjoy his social life , look for knowledge , buy all the precious books and resources specially those related to his specialization i.e., history, and get every piece of knowledge he found and never waste it..Jawad Ali wrote approximately 102 research and translated 85 books some of which are available but others are not .He showed a real interest in writing prose and poetry ,and mainly focused on geography, agriculture etc..Essentially, it must be said that all those who knew Jawad Ali and met him said that he was a man of deeds.Jawad Ali is known by his book "AL-Mufasal of Arabs History in the Pre-Islamic Period" He wrote this book on chapters and finished writing it within forty years .Each chapter deals with a specific field concerning the life of Arabs in the pre-Islamic period i.e., the religious field and the social field.Jawad Ali wrote other books some of which are bulky others are not.In his writings, Jawad Ali depended on books, letters, personal experience and other resources .However ,he depended on more than 700 recourses known eight by its author or by its title and also on pictures and stones of different historical ages..In addition to that, he translated some of the valuable books from: French, English, German, Persian and Latin into Arabic.Jawad Ali wrote on different topics i.e., the pre-Islamic period, Arabs and the Islamic period , pray ,AL-Mahdi and his four messengers and other topics.Academically, "AL-Mufasal " is one of his best books ,it might have some slips but still it represents the history of the pre-Islamic period and reflect it greatly .The title of the book goes inline with its contents and no researcher can ignore the valuable information found in it .Jawad Ali wrote this book to be one of the extra ordinary resources that must be read by any historian or student of history To sum up, it is wort noting that Jawad Ali did his best to write"AL Mufasal" in a way that makes it a star in the sky of history.